Obsession Falls [large type] - Dodd, Christina (Center Point Large Print, 2015)
"Taylor Summers witnesses the death threat to a young boy, and sacrifices herself to distract the killers. Her reward is a life in ruins, on the run in the wilderness. Finding refuge in Virtue Falls, she must enlist the help of the man who does not trust her to defeat the man who would destroy her"--